2019
DOI: 10.1186/s12902-019-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

Overtime trend of thyroid hormones and thyroid autoimmunity and ovarian reserve: a longitudinal population study with a 12-year follow up

Abstract: Background Ovarian reserve, vital for reproductive function, can be adversely affected by thyroid diseases. Despite alternations of thyroid hormones with ageing, data on interactions between the overtime trend of thyroid functions and ovarian reserve status has rarely been reported. We aimed to examine the overtime trend of thyroid hormones, thyroid peroxidase antibody (TPO Ab) and their associations with ovarian reserve status, identified by levels of age specific anti-mullerian hormone (AMH) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…These conflicting results could be connected with the heterogeneity of the groups and with the fact that it was a retrospective study. On the other hand, in the longitudinal population study with 12 years of follow-up, it was observed that women with lower serum concentration of AMH had higher serum levels of TPOAbs at baseline with a tendency to increasing autoimmunity in comparison to women with better ovarian reserve status (43). As it was mentioned in the Introduction section, the serum concentration of AMH is considered as one of the most sensitive indicators of ovarian reserve; therefore, we can speculate based on the previous observation that the presence of TPOAbs in women with PCOS observed in our study could be connected with decreased fertility.…”
Section: Discussionmentioning
confidence: 98%
“…These conflicting results could be connected with the heterogeneity of the groups and with the fact that it was a retrospective study. On the other hand, in the longitudinal population study with 12 years of follow-up, it was observed that women with lower serum concentration of AMH had higher serum levels of TPOAbs at baseline with a tendency to increasing autoimmunity in comparison to women with better ovarian reserve status (43). As it was mentioned in the Introduction section, the serum concentration of AMH is considered as one of the most sensitive indicators of ovarian reserve; therefore, we can speculate based on the previous observation that the presence of TPOAbs in women with PCOS observed in our study could be connected with decreased fertility.…”
Section: Discussionmentioning
confidence: 98%
“…After adjustment for thyroid autoimmunity and age, TSH < 3.0 mIU/l in infertile euthyroid patients has been associated with significantly higher AMH than in patients with TSH ≥3.0 mIU/l [26]. Moreover, higher levels of thyroperoxidase antibodies (TPOAb) have been observed in women with a lower ovarian reserve, with a positive trend of these antibodies over time, indicating that this group may be at higher risk of hypothyroidism over time [27]. Kuroda et al [28] also reported a clear association between elevated TSH and reduced AMH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, none statistically relevant difference in circulating THs was detected at the baseline whereas the AbTPO antibodies concentration was higher in women included in Q1. A progressive decrease of fT4 and an increased level of AbTPO antibodies were detected in all the quartiles over time [ 93 ]. Accordingly, a previous study, involving about 1000 Chinese women, reported the increase of AbTPO antibodies concomitant with idiopathic DOR [ 94 ].…”
Section: Circulating Th/tsh Levels and Premature Ovarian Dysfunctimentioning
confidence: 99%